Are U.S. firms using more short-term debt? - Byun, Seong K.; Lin, Zhilu; Wei, Siqi (Journal of Corporate Finance, 2021)
We show that, despite the sharp but temporary decline around the financial crisis of 2007–08, corporate debt maturity has risen significantly in the last two decades, erasing much of the secular decline from the 1980–90s documented in the literature. The reversal in debt maturity trend is driven by the rise in the use of intermediate-term debt among medium and large-sized firms. The low interest rates observed in the last two decades and the decline in the demand for long-term corporate bonds partly explains the rise in intermediate-term debt.